2021
DOI: 10.1177/2333392820988404
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incentive Management System on Turnover Rate, Job Satisfaction and Motivation of Medical Laboratory Technologists

Abstract: Objectives: We investigated factors affecting turnover and assessed satisfaction with an existing Incentive Management System and to which extent it motivates employees. We also provide recommendations to improve the Incentive Management System. Methods: A cross-sectional questionnaire study utilizing a convenience sample from of a population of 250 Medical Laboratory Technologists. Findings: 100 medical laboratory technologists responded to the survey. We found discrepancy in wage allocation to be the most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Participants in the study cited the lack of compensation as a factor that caused some to consider leaving their positions or seeking alternative employment. This finding aligns with a study examining turnover rates among MLTs which found low salaries and low annual raises are the primary factors contributing to turnover [69].…”
Section: Pandemic Stressorssupporting
confidence: 90%
“…Participants in the study cited the lack of compensation as a factor that caused some to consider leaving their positions or seeking alternative employment. This finding aligns with a study examining turnover rates among MLTs which found low salaries and low annual raises are the primary factors contributing to turnover [69].…”
Section: Pandemic Stressorssupporting
confidence: 90%
“…In addition, researchers and practitioners have pointed out that an organization can motivate its workers through various forms of incentive systems to improve and contribute to the organization's performance. Moreover, incentive systems can be used as a strategy to retain employees [10] or as a recruitment tool [11]. Additionally, organization systems should review and evaluate their employees' performance and productivity fairly and accurately [12,13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study established that actions need to be taken to improve the level of motivation among medical laboratories to promote a good quality of the healthcare service [ 19 ].…”
Section: Introductionmentioning
confidence: 99%